Current treatment strategies in malignant pleural mesothelioma with a treatment algorithm - (:unkn) unknown (VIA MEDICA, 2019)
Malignant pleural mesothelioma (MPM) is a rare disease with a poor prognosis. The main therapeutic options for MPM include surgery, chemotherapy, and radiation therapy (RT). Although multimodality therapy has been reported to improve survival, not every medically operable patient is able to undergo all recommended therapy. With improvements in surgical techniques and systemic therapies, as well as advancements in RT, there has been a potential new paradigm in the management of this disease. In this review, we discuss the current literature on MPM management and propose a functional treatment algorithm.
Keywords: mesothelioma; surgery; chemotherapy; radiotherapy; MULTICENTER PHASE-II; SINGLE-INSTITUTION EXPERIENCE; MODULATED RADIATION-THERAPY; EXTRAPLEURAL PNEUMONECTOMY; TRIMODALITY THERAPY; HEMITHORACIC RADIATION; PEMETREXED PLUS; OPEN-LABEL; INTERNATIONAL-ASSOCIATION; INDUCTION CHEMOTHERAPY